2018
DOI: 10.3390/nu10111618
|View full text |Cite
|
Sign up to set email alerts
|

The Immunomodulatory and Anti-Inflammatory Role of Polyphenols

Abstract: This review offers a systematic understanding about how polyphenols target multiple inflammatory components and lead to anti-inflammatory mechanisms. It provides a clear understanding of the molecular mechanisms of action of phenolic compounds. Polyphenols regulate immunity by interfering with immune cell regulation, proinflammatory cytokines’ synthesis, and gene expression. They inactivate NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells) and modulate mitogen-activated protein Kinase (MAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
835
0
29

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,236 publications
(883 citation statements)
references
References 219 publications
(267 reference statements)
19
835
0
29
Order By: Relevance
“…PGE 2 is an effective suppressor of TNF‐α production by the inflammatory cells . Also, it was demonstrated that IND increased NF‐κB, as disclosed also in our immunohistochemical findings, with subsequent stimulation of the production of the pro‐inflammatory cytokines as TNF‐α and IL‐1β . Another prospective explanation for the increased levels of TNF‐α and IL‐1β, is that the increased mitochondrial fission, by IND, might be a cause of increased production of pro‐inflammatory cytokines via increased ROS production and NF‐κB expression, these also were explored in our results.…”
Section: Discussionsupporting
confidence: 75%
“…PGE 2 is an effective suppressor of TNF‐α production by the inflammatory cells . Also, it was demonstrated that IND increased NF‐κB, as disclosed also in our immunohistochemical findings, with subsequent stimulation of the production of the pro‐inflammatory cytokines as TNF‐α and IL‐1β . Another prospective explanation for the increased levels of TNF‐α and IL‐1β, is that the increased mitochondrial fission, by IND, might be a cause of increased production of pro‐inflammatory cytokines via increased ROS production and NF‐κB expression, these also were explored in our results.…”
Section: Discussionsupporting
confidence: 75%
“…Polyphenols have been established to have antioxidant properties [22] and possess a variety of other specific biological effects. Therefore, these components have the potential to prevent diseases through mechanisms that are dependent and independent of their antioxidant properties [23][24][25].…”
Section: Glucose Homeostasis: Role Of Insulinmentioning
confidence: 99%
“…Several polyphenols such as curcumin, quercetin, and catechins exhibit their effects on the balance between secretion of pro-inflammatory and anti-inflammatory cytokines. They inhibit the release of pro-inflammatory cytokines and activate anti-inflammatory cytokines' production [52]. However, curcumin has shown the ability to inhibit the production of TNF-α and some pro-inflammatory interleukins such as IL-1 and IL-6, while increasing the production of anti-inflammatory IL-10 [49,53,54].…”
Section: Discussionmentioning
confidence: 99%